ORAL HEALTH STATUS OF INDONESIAN CHILDREN ( Scoping Review ) - Utami, Sri Pandu Pandu (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2023)
Background: Teeth and mouth are important organs that must be kept clean. People still think that the oral cavity is a small part of the body so that awareness of maintaining oral health is still low. Oral health plays an important role in general health. Many studies have reported various risk factors associated with the incidence of dental caries . Objective : To determine the oral health status of Indonesian children. Method : The method used is to collect sources of information obtained from bibliographic searching taken from Pubmed , Google Scholar and Science Direct. Result : Oral health status is generally expressed in terms of prevalence dental caries and periodontal disease. Conclusion: Oral health status and oral health behavior differ at different ages. Dental caries has several negative effects, particularly on children's lives, through reduced masticatory performance and general appearance, and this is reflected in their growth and development.